HOSPITAL SUNGAI BULOH'S EXPERIENCE IN USING FIXED INSULIN INFUSION FOR DIABETIC EMERGENCIES - N, Lavanya; WMS, Farrah; Y, Yusniza (Journal of the ASEAN Federation of Endocrine Societies, 2019)
INTRODUCTION Diabetic ketoacidosis (DKA) and hyperglycemic hyperosmolar state (HHS) are diabetic emergencies that cause high mortality and morbidity. The mainstay of treatment for diabetic emergencies is insulin and fluid therapy. Various methods of insulin initiation are commenced in different healthcare settings based on their respective standard practice guidelines. CASE A clinical audit was carried out based on the data of patients age 12 to 80 years admitted for diabetic emergencies in Hospital Sungai Buloh for a period of 11 months (May 2018 to April 2019). All patients were commenced on the fixed insulin infusion scale regime at point of diagnosis. Results showed that the average time of resolution of DKA/ HHS of less than 24 hours was achieved by almost 87% of total patients who were admitted for diabetic emergencies from May 2018 to April 2019. CONCLUSION Our experience of using the fixed insulin infusion scale regime in the treatment of diabetic emergencies has shown good outcomes.